Beliefs and attitudes towards lifestyle change and risks in primary care - a community-based study - Pekka Mäntyselkä; Hannu Kautiainen; Juhani Miettola (BMC, 2019)
Abstract Background Promoting a positive lifestyle change is a challenge for primary health care. The aim of this study was to analyze health and risk-related beliefs and attitudes in relation to lifestyle and lifestyle change in a rural community. Methods The study was based on a five-year follow-up data of the Lapinlahti study (N = 361). The same structured questionnaire was used at baseline and follow-up with lifestyle items. These were ranked as unhealthy (− 1), neutral (0) or healthy (+ 1). At baseline, participants took a stand on 29 statements related to beliefs and attitudes towards health and health promotion on a 5-point Likert scale. A factor analysis yielded two attitude factors (Factor 1 = underrating risks/resistant to change); (Factor 2 = helplessness/pessimism). The factors were divided into tertiles. Results There was a linear positive trend (P < 0.001) in baseline lifestyle scores between the tertiles of Factor 1. A positive follow-up change of lifestyle score was found in all tertiles of Factor 1. For Factor 2, the difference between tertiles at baseline was non-significant. There was a significant positive change in all tertiles of Factor 2. Those who were underrating/ resistant but not helpless/pessimistic had the most significant positive lifestyle change. Those who were underrating/resistant and helpless/pessimistic did not improve their lifestyles. Conclusions Beliefs and attitudes are related to lifestyle. Subjects with underrating and resistant attitudes with pessimism/helplessness seem to have a low potential for lifestyle change while those with resistant attitudes without pessimism and helplessness may have the most significant potential for lifestyle change. These findings suggest that it is possible to identify different groups of people with different needs and readiness and ability for health behavior change.